Can one long peritoneal dwell with icodextrin replace two short dwells with glucose? - Stachowska-Pietka, Joanna; Waniewski, Jacek; Olszowska, Anna; Garcia-Lopez, Elvia; Yan, Junfei; Yao, Qiang; Wankowicz, Zofia; Lindholm, Bengt (Frontiers in Physiology, 2024)
Background: Due to slower dissipation of the osmotic gradient, icodextrin-based compared to glucose-based solutions can improve water removal. We investigated scenarios where one icodextrinbased long dwell (Extraneal) replaced two glucose-based exchanges.The three-pore model with icodextrin hydrolysis was used for numerical simulations of single exchange to investigate the impact of different peritoneal dialysis schedules on fluid and solute removal in patients with different peritoneal solute transfer rate (PSTR). We evaluated water removal (ultrafiltration, UF), absorbed mass of glucose (AbsGluc) and carbohydrates (AbsCHO, for glucose and glucose polymers), ultrafiltration efficiency (UFE=UF/ AbsCHO) per single exchange and specified dwell time, and removed solute mass for sodium (ReNa), urea (ReU), and creatinine (ReCr) for single peritoneal exchange with Extraneal 7.5% icodextrin (Extraneal®) and glucose-based solutions (1.36% and 2.27%) and various dwell durations in patients with fast and average PSTR.Results: Introducing 7.5% icodextrinExtraneal for the long dwell to replace 1 of 3 or 4 glucose-based exchanges per day leads to increased fluid and solute removal and higher UF efficiency for studied transport groups. Replacing two glucose-based exchanges with one icodextrinExtraneal exchange provides higher or similar water removal and higher sodium daily removal but slightly lower daily removal of urea and creatinine, irrespectively of the transport type present in case of reference prescription with 3 and 4 daily exchanges.Conclusions: One 7.5% icodextrinExtraneal can replace two glucose solutions. Unlike glucose-based solutions, it resulted only in minor differences between PSTR groups in terms of water and solute removal with UFE remaining stable up to 16 hours.